A new methodological framework for evaluating flexible options at airport passenger terminals. Issue 1 (March 2020) - Magalhães, Liliana; Reis, Vasco; Macário, Rosário
Highlights: Flexibility has been proposed as an alternative to airport development as it increases airports' resilience to unexpected events. The benefits of flexibility have been discussed at a conceptual level as research which refers to ways of measuring the benefits of flexibility is almost inexistent. The framework proposed to support the incorporation of flexibility is meant to guide airport managers assessing the plausibility of alternatives in improving the efficiency of airport's processes. The framework was applied to Terminal 2 of the Lisbon Airport and the results evidence that flexibility can increase the efficiency by reducing the waiting times, which will increase the passengers' dwelling time. The costs of flexible options can be compensated by the increase in the non-aeronautical revenues. Abstract: Flexibility has been proposed as a suitable alternative or a complement to the traditional airport development approach based on Master Plans. Flexibility increases airports' resilience to unexpected or unforeseen events such as economic recessions, regulatory restrictions or technological developments, to name a few. Although the benefits of flexibility have been discussed, the debate has thus far been conducted at the conceptual level. Furthermore, research which refers to ways of measuring the benefits of flexibility is almost inexistent. This manuscript proposes a novel framework to support the incorporation of elements of flexibility in the airport development plan. The framework was primarily developed for cases of extension – i.e., when expansion is not an option. It is organised in three phases: 1) definition of the decision inputs, scenarios and flexible options, 2) ex-ante operational evaluation and, 3) ex-ante economic evaluation. The framework is meant to guide airport managers assessing the plausibility of alternatives in keeping or improving the efficiency of airport's processes. An application of the framework is presented. The case study is the Terminal 2 of the Lisbon International Airport. The objective of the use of this case study is twofold: 1) to exemplify the applicability of the framework, and; 2) validate the framework together with the interviews that we conducted with airport practitioners. The results evidence that flexibility can increase the efficiency by reducing the waiting times, which will increase the passengers' dwelling time. The costs are compensated by the increase in the non-aeronautical revenues.